Pathogenetic Aspects of Systemic Sclerosis: A View Through the Prism of B Cells - Melissaropoulos, Konstantinos; Iliopoulos, George; Sakkas, Lazaros I.; Daoussis, Dimitrios (Frontiers in Immunology, 2022)
Systemic sclerosis (SSc) is a rare fibrotic rheumatic disease, associated with psychological distress and increased morbidity and mortality due to skin involvement and internal organ damage. The current understanding of the complex pathogenesis is yet incomplete and disease therapeutic algorithms are far from optimal. Immunologic aberrations are considered key factors for the disease, along with vascular involvement and excess fibrosis. Adaptive immunity and its specialized responses are an attractive research target and both T and B cells have been extensively studied in recent years. In the present review, the focus is placed on B cells in SSc. B cell homeostasis is deranged and B cell subsets exhibit an activated phenotype and abnormal receptor signaling. Autoantibodies are a hallmark of the disease and the current perception of their diagnostic and pathogenetic role is analyzed. In addition, B cell cytokine release and its effect on immunity and fibrosis are examined, together with B cell tissue infiltration of the skin and lung. These data support the concept of targeting B cells as part of the therapeutic plan for SSc through well designed clinical trials.